2009
DOI: 10.1159/000232199
|View full text |Cite
|
Sign up to set email alerts
|

Association of (Pro)renin Receptor mRNA Expression with Angiotensin-Converting Enzyme mRNA Expression in Human Artery

Abstract: Background/Aims: A significant role of (pro)renin receptor in the pathogenesis of end-organ damage has been suggested only in animal studies. This study was conducted to examine the mRNA expression of (pro)renin receptor in human artery. Methods: In 141 kidney failure patients, the mRNA was harvested from arterial fragments obtained during surgery constructing an arteriovenous access for hemodialysis therapy, and expression levels of (pro)renin receptor and other components of the renin-angiotensin system were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 69 publications
(59 reference statements)
2
8
0
Order By: Relevance
“…Consistent with the findings of the study of Takemitsu et al [20], neither plasma prorenin level nor (P)RR expression in PBMCs correlated with SBP and DBP in non-DM-HD patients in the present study. Hirose et al [21] Clin Exp Nephrol (2011) 15:398-404 401 reported the association of (P)RR gene polymorphism with SBP and DBP in Japanese men.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Consistent with the findings of the study of Takemitsu et al [20], neither plasma prorenin level nor (P)RR expression in PBMCs correlated with SBP and DBP in non-DM-HD patients in the present study. Hirose et al [21] Clin Exp Nephrol (2011) 15:398-404 401 reported the association of (P)RR gene polymorphism with SBP and DBP in Japanese men.…”
Section: Discussionsupporting
confidence: 92%
“…Takemitsu et al [20] also reported that plasma prorenin concentration correlated with PRA, plasma AT I level, plasma AT II level and plasma Ald level in non-DM-HD patients. In the present study, plasma prorenin level did not correlate with PRA, plasma AT I level, plasma AT II level or plasma Ald level.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…32 The plasma prorenin levels in diabetic patients were significantly higher than those in non-diabetic patients. Nevertheless, arterial (P)RR expression was similar in diabetic and non-diabetic patients, suggesting that the negative feedback mechanism of the (P)RR observed in cultured cells 26,27 does not work in diabetic patients.…”
Section: Arterial Mrna Levels In Patients With Stage 5 Chronic Kidneymentioning
confidence: 89%